Of Gardens: An essay - Bacon, Francis, 1561-1626; Pissarro, Esther, 1870-1951; Pissarro, Lucien, 1863-1944 (Salt Lake City, UT : Project Gutenberg, 2014)
"Of Gardens: An essay by Francis Bacon" is a reflective essay likely written in the early 17th century. This work explores the aesthetics and importance of gardens, presenting them as vital elements of civilized living and human enjoyment. Bacon articulates his vision for ideal gardens, emphasizing the interplay of beauty and functionality throughout the seasons. In this essay, Bacon outlines a comprehensive design for an expansive garden, integrating various types of plants to ensure beauty year-round. He discusses the importance of specific flowers and trees, detailing how to arrange them for both aesthetic pleasure and practical use. He advocates for a structured layout that includes distinct areas such as a green entrance and a wild heath, while also emphasizing the importance of fountains and thoughtful landscaping. Through his writings, Bacon reflects on gardens as not merely a collection of plants but as a profound source of pleasure and renewal for the human spirit, highlighting their role in the larger context of architecture and nature. (This is an automatically generated summary.)
Release date is 2014-09-25
Turgut Dincer
Keywords: Gardens